Distribution of Trace Elements in Sediments and Biota of Songkhla Lake, Southern Thailand - Siriporn, Pradit (ScienceDirect, 2016)
The concentrations of Co,Ni, Cu, Zn, Cd, Pb,As, Fe, Mn, and Al were determined in sediments and biota of Songkhla Lake, a shallow coastal lagoon located in southern Thailand. In June 2006, surface sediments were sampled in 44 stations in the three sections of the lake (inner-, middle-, and outer sections). Sediment cores were also sampled in 13 stations in three cross-sections of the lake. In surface sediments, trace and major elements, organic matter, sediment grain size analysis, and sulfides were determined, and in the sediment cores, redox profiles were made. Soil samples were also collected at garbage dumping sites in the vicinity of the lake. In addition, the metal accumulation in two catfish species (Arius maculatus and Osteogeneiosus militaris) and the crustacean (Apseudes sapensis) was also investigated. Trace element concentrations in sediments of Songkhla Lake show that, especially the Outer section of the lake, in particular the sediments atthe mouths of the Phawong, U-Taphao, and Samrong Canals are significantly enriched with trace elements due to municipal, agricultural, and industrial discharges entering the lake through the canals. Aluminumnormalized enrichment factors throughout the lake vary from 0.4 to 1.7 for Ni, 0.3 to 3.3 for Cu, 0.2 to 7 for Zn, 0.1 to 14 for As, 1 to 24 for Cd, 0.7 to 6.8 for Pb, and 0.1 to 7.8 for Mn. Correlations between the elements and sediment characteristics show that Cu, Zn, Cd, and Pb are essentially associated with the sulfide fraction; that Ni and Co are predominantly bound to the clay minerals and iron oxy-hydroxides, and that As is principally bound to iron oxy-hydroxides. The accumulation of trace elements between muscle tissue and liver and eggs of A. maculatus and O. militaris is element-specific, but concentrations of trace elements in fish muscle tissue are well within the limits for human consumption.